Implementation of Dormitory Activities in Improving Religious and Disciplinary Character - Nurhasanah, Nurhasanah; Almi, Fitria; El-Rahma, Neysa Rasionalis; Rahman, Ikhwan (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2024)
This study aims to, 1) find out the form of boarding activities of students at Bintang Sekolah Al-Quran, 2) find out the implementation of boarding activities in improving the religious and disciplinary character of students at Bintang Sekolah Al-Quran, 3) find out the supporting and inhibiting factors of improving the religious and disciplinary character of students at Bintang Sekolah Al-Quran. This research uses a qualitative method using a case study approach. The data collection techniques used are observation, interviews, and documentation. Data sources were taken from eleven informants through in-depth interviews with informants. The eleven informants consisted of leaders, dormitory coaches, male and female students. The results of this study are, 1) the form of dormitory activities at Bintang Al-Quran School in Improving the Religious and Disciplinary Character of students, namely: tahajud prayer, dhikr together, picket, halaqah, congregational prayer, recitation of the Koran, hadith study, motivational study, muhadarah, Sunday morning activities. 2) related to the process of implementing boarding activities in improving the religious and disciplinary character of students, which is carried out every day starting from the students waking up at 04.00 until resting again at 22.00 WIB. 3) The supporting factors are: full support from the leadership of Bintang Sekolah Al-Qur'an, the quality of teaching from ustad/zah at Bintang Sekolah Al-Qur'an, parental support, and adequate facilities.